The narrative program in their novel is a semiotic study (Journal of the College of Basic Education, 2023)
The novel "These People" by Majid Tobia is one of the novels that symbolically expresses the nature of the state in Egyptcountries of the Arab world; and immersed in coding as well as the generalization of the expressed model; I suggested the novelThe name of the writer is reversed (Dijem) to express the head of the state and its leader, and the name of the father of the writer is reversed (Aybut) to expressthe name of the country concerned. This novel can be considered a kind of satirical irony or comedyblack politics; And it remained immune to an analysis that reveals the nature in which events are organized in a programA definite narrative that, with blissful praise, intends to reveal a very definite goal; Not a narrative program inthe novel; Benefiting from the narrative semiotics presented by the Paris Semiotic School. Research will be of interestBy analyzing the narrative level among the three levels in the semiotic analysis; leaving level analysisThe rhetorical and deep semantic level of another occasion.